Angola : Second and Third Reviews Under the Stand-By Arrangement and Request for Waivers of Nonobservance of Two Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2010)
Angola has made significant progress toward economic stabilization. Under the Stand-By Arrangement (SBA), the government's key fiscal anchor is the non-oil primary fiscal deficit (NOPD), and the revised 2010 budget is determined to avoid any increase in the non-oil primary deficit. Policy discussions focused on the fiscal stance for the remainder of 2010, and in 2011, the resolution framework for clearing domestic arrears payment, reforming the tax system, strengthening the asset-liability management capacity, and improving the tools for monetary management.